Parthera pardus - Masseti, Marco (Zenodo, 2009)
Leopard, Parthera pardus (Linnaeus, 1758) Fig. 12 As regards this felid, I was able to examine only the skin of an adult male killed at Nabi Yunes, Slonfeh, north-western Syria, in 1959 (ZFMK n. 64.1171, see Lehmann 1965), and to collect direct information about the disappearance of the last individuals from the same region. In the territories of northern Syria where the species was last reported, the Asia Minor leopard, P. pardus tulliana Valenciennes, 1856, is documented but it cannot be ruled out that the Arabian leopard, P. pardus nimr Hemprich & Ehrtenberg, 1833, may also have occurred in the desert regions of southern Syria. In the Levant, felids of the latter subspecies are still dispersed along the shores of the Dead Sea, and in the Negev desert (Mendelssohn 1989; Masseti 2000a; Shalmon 2004). The last Syrian leopard is reputed to have been killed in 1963, in the vicinity of the village of Bab Jannè (= “ the gate of paradise ”), Slonfeh, on the Alawit Mountains, about 20 km from the Turkish border (Masseti 2000a). According to Ahmad Hamud of the Arab Forest and Range Institute of Lattakia (AFRI) (1994, pers. comm.), this specimen was killed by a forest guard of the Kharafan family in the forest of Cilician fir, Abies cilicica (Ant. et Klotsch.) Carr. It is perhaps interesting to recall that the same Figure |2. • Leopard, Panthera pardus (Linnaeus, 1758); · Caracal, Caracal caracal (Schreiber, 1776). area is also the last Syrian stronghold of the Kurdish roe deer, Capreolus capreolus coxi (Cheesman and Hinton 1923) (Masseti 2000b and 2004). Remarks In the course of this research it was possible to gather information on the current diffusion of 15 species of carnivore ranging in size from the wolf to the weasel, and not including the leopard. It was, not possible to ascertain the occurrence of the Blandford fox, Vulpes cana Blandford, 1877, in Syria. The species was first recorded from the western Near East by Ilani (1983), and there is no previous information from this area. Today the western limit of its distribution is found in the southern Levant (Ginsberg and Macdonald 1990), where it inhabits the cliffs of the desert region from Aqaba up to the southern Jordan valley (Abu Baker et al. 2004; Shalmon 2004). However, as in the recent case of the sand cat in the Tadmor desert, it cannot be ruled out that further studies might document the presence of Vulpes cana in some of the rocky regions of Syria. Nor was it possible to obtain any information about the ratel or honey badger, Mellivora capensis (Schreber, 1776), and we should recall that Kumerloeve (1975) too was unable to confirm the occurrence of this species from the Syrian territories. This is not to say, however, that the species is to be considered as completely absent from the country, otherwise it would be impossible to explain its fairly well-documented occurrence in neighbouring Jordan (see Amr, 2000), and Israel (see Shalmon, 2004). In this case too, it cannot be ruled out that the absence of specific sightings/reports for Syria could plausibly be attributed to the absence of targeted studies. Nor should we overlook the fact that in the entire Near East this species is frequently persecuted, being poisoned and hunted by bee farmers because it of the damage it causes to beehives (Shalmon, 2004). Nor was any information obtained about the occurrence of the smooth-coated Indian otter, Lutrograle perspicillata (Geoffroy, 1826) along the Syrian course of the Euphrates. In any case, however, the Near Eastern range of this Middle and Far Eastern species has been indicated as limited to southern Mesopotamia (Harrison 1968; Harrison and Bates 1991; Wozencraft 2005; Karami et al. 2008). The question of the possible presence of representatives of the Lynx genus in modern-day Syria remains open (see Aymerich 1991). One specimen characterised by the “pardina” phenotype was reported by Oriani (2000) from Tadmor (= Palmyra), who stated that: “ In Syria the species was not recorded prior to this work ”. Local hunters at Deir-ez-Zor refer to the occurrence of felids of this type on Jebel Ablasis and Jebel Abdul-Aziz, between the Balik and Khabur, rivers in the northern Djazireh, not far from the southern Turkish border. The same hunters declare that the main difference between this carnivore and the jungle cat consists in the fact that the former is maculated, with black spots. But other spotted felids did also occur in the past in this geographical area. As a consequence of the extinction of the large felids and the progressive rarefaction of wolves, the majority of carnivores presently occurring in Syria are represented by species that are fully adapted to living in areas influenced by man. Jackals, foxes, wild and jungle cats, mongooses and several mustelids are carnivores that humans have accepted as neighbours, while also being those that are most adept at avoiding contact with man (cf. Osborn and Helmy 1980; Ragni et al. 1999, Masseti 1995, 2002a). These carnivores are principally represented by generalist species which can thrive in a wide variety of environmental conditions and can exploit a range of different resources Thus, they are able to vary their diets according to local and seasonal food availability. Frequently, for example, in the Mediterranean region the stone marten can be found behaving as a full commensal of man in urban areas (cf. Masseti 2002b) and it is also well known that weasels in the Nile delta are almost completely commensal with man (see Osborn and Helmy 1980). : Published as part of Masseti, Marco, 2009, Carnivores of Syria, pp. 229-252 in ZooKeys 31 (3) on pages 245-246, DOI: 10.3897/zookeys.31.170, http://zenodo.org/record/576592 : {"references": ["Lehmann E von (1965) Uber die Saugetiere im Waldgebiet NW-Syriens. Sitzungsberichte der Gesellschaft Naturforschender Freunde zu Berlin (N. F.), 5 (1): 22 - 38.", "Mendelssohn H (1989) Felids in Israel. Cat News, 10: 2 - 4.", "Masseti M (2000 a) Wild cats (Mammalia, Carnivora) of Anatolia. With some observations on the former and present occurrence of leopards in south-eastern Turkey and on the Greek island of Samos. Biogeographia: 20: 607 - 618.", "Shalmon B (2004) Mammals. In: Dolev A, Perevolotsky A (Eds): The Red Book of the Vertebrates in Israel. The Israel Nature and Parks Authority and the Society for the Protection of Nature in Israel, Jerusalem: 211 - 289.", "Masseti M (2000 b) Note on a Near-Eastern relic population of roe deer, Capreolus capreolus (L., 1758) (Mammalia, Artodactyla). Biogeographia, 20: 619 - 623.", "Masseti M (2004) Artiodactyls of Syria. Zoology in the Middle East, 33: 139 - 148.", "Ilani G (1983) Blanfords fox, Vulpes cana Blanford, 1877, a new specie sto Israel. Israel Journal of Zoology, 32: 150.", "Ginsberg JR, Macdonald DW (1990) Foxes, wolves, jackals and dogs: an action plan for the conservation of Canids. IUCN. Gland (Switzerland): 116 pp.", "Abu Baker MA, Al Omari K, Qarqaz M, Khaled Y, Yousef M, Amr ZS (2004) On the current status and distribution of Blanford'fox, Vulpes cana Blanford, 1877, in Jordan (Mammalia: Carnivora: Canidae). Turkish Journal of Zoology, 28: 1 - 6.", "Kumerloeve H (1975) Die Saugetiere (Mammalia) Syriens und des Libanon. Veroff. Zool. Staatssamml. Munchen, 18: 159 - 225.", "Amr ZS (2000) Jordan Country Study on Biological Diversity. Mammals of Jordan. United Nations Environment Programme / National Library, Amman: 100 pp.", "Harrison DL (1968) The mammals of Arabia. Vol. II. Carnivora - Artiodactyla - Hyracoidea. Ernest Benn Ltd, London: 380 pp.", "Harrison DL, Bates PJJ (1991) The Mammals of Arabia. Harrison Zoological Museum, Sevenoaks (England): 354 pp.", "Wozencraft W (2005) Order Carnivora. In: Wilson DE, Reeder DM (Eds) Mammal Species of the World. A Taxonomic and Geographic Reference. Third Edition. Volume 1. The John Hopkins University Press, Baltimore: 532 - 628.", "Karami M, Hutterer R, Benda P, Siahsarvie R, Krystufek B (2008) Annotated check-list of the mammals of Iran. Lynx, n. s., 39 (1): 63 - 102.", "Aymerich M (1991) Situacion del lince boreal en Europa. Quercus, 61: 13 - 16.", "Oriani A (2000) Le linci del Caucaso e dell'Asia Occidentale. Atti Soc. it. Sci. nat. Museo civ. Stor. nat. Milano, 141 / 2000 (I): 51 - 64.", "Osborn DJ, Helmy I (1980) The contemporary land mammals of Egypt (including Sinai). Feldiana Zoology, 5: 1 - 579.", "Ragni B, Masseti M, Roussos T, Belardinelli A, Cicconi P (1999) The carnivores of the island of Crete, Greece). Contributions to the Zoogeography and Ecology of the Eastern Mediterranean Region, 1: 117 - 123.", "Masseti M (1995) Quaternary biogeography of the Mustelidae family on the Mediterranean islands. Hystrix, (N. S.) 7 (1 - 2): 17 - 34.", "Masseti M (2002 a) Uomini e (non solo) topi. Gli animali domestici e la fauna antropocora. Firenze University Press / Universita di Firenze, Firenze: 337 pp.", "Masseti M (2002 b) The non-flying terrestrial mammals of the Dodecanese islands. In: Masseti M. (Ed): Island of deer. Natural history of the fallow deer of Rhodes and of the vertebrates of the Dodecanese (Greece). Environment Organisation of the City of Rhodes, Rhodes: 89 - 98."]}